2022
DOI: 10.3390/su14095125
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership and Innovative Behavior: Mediating Role of Voice Behavior and Moderated Mediation Role of Psychological Safety

Abstract: Organizations increasingly emphasize and require their members to engage in innovative behavior because it is directly associated with organizational sustainability and survival. This study aims to address whether ethical leadership enhances subordinates’ innovative behavior and investigates the mediating role of voice behavior in promoting innovative behavior. Psychological safety was tested to moderate the mediating effect of voice behavior on the relationship between ethical leadership and innovative behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…The results indicate that ethical leadership positively influences employees' innovative work behavior, implying that employees' innovative work behavior becomes more active when leaders are ethical and moral. This result is also consistent with previous studies where the authors concluded that ethical leadership is important in promoting the innovative work behaviors of employees [2,3,91]. Through empirical analysis, this study also confirms the multiple mediating effects of psychological safety and work engagement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results indicate that ethical leadership positively influences employees' innovative work behavior, implying that employees' innovative work behavior becomes more active when leaders are ethical and moral. This result is also consistent with previous studies where the authors concluded that ethical leadership is important in promoting the innovative work behaviors of employees [2,3,91]. Through empirical analysis, this study also confirms the multiple mediating effects of psychological safety and work engagement.…”
Section: Discussionsupporting
confidence: 92%
“…Although there is a growing body of research on leadership's impact on creative outcomes and innovation, most studies have focused on leaders' effects on employee creativity, with limited research on their effects on innovative work behaviors [4,92]. In particular, the impact of ethical leadership on employee task performance and innovative behavior needs to be further explored [3]. In doing so, we responded to recent calls [2,3,91] to further explore the impact of ethical leadership on employees' innovative work behaviors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in recent COVID-19 pandemic and Omicron situation, the importance of organizational members' innovative behavior was emphasized by [56]. It is expected that organizational climate has an influence on decision-making.…”
Section: Limitations and Suggestions For Future Studiesmentioning
confidence: 99%
“…In terms of outcome variables, psychological safety is an important factor that influences employees’ engagement behaviors, individual/team learning behaviors, innovation behaviors like new ideas ( Carmeli et al, 2014 ), constructive behaviors ( Carmeli et al, 2010 ; Edmondson, 2016 ), and knowledge sharing ( Siemsen et al, 2009 ). Moreover, psychological safety acts as a mediating variable between management style and creativity ( Jiang and Gu, 2016 ); corporate social responsibility and employee creativity ( Kim et al, 2021 ); and ethical leadership and innovation behavior ( Jin et al, 2022 ). Current research has focused on the effects of psychological safety on employees’ and teams’ learning, innovation, and performance; However, it has not sufficiently explored the effects of other factors at the individual level.…”
Section: Literature Reviewmentioning
confidence: 99%